Windows 8 for dummies - Rathbone, Andy (--For dummies., 2012)
The bestselling tech book of all time is now updated for Windows 8 Microsoft Windows, the operating system that runs nearly 90 percent of the world's computers. Windows 8 will offer new interface updates, cloud-based services, and much more.